ARMED BANDITRY IN ADARALAND: A STUDY OF HUMANITARIAN CRISIS AND THE PLIGHT OF INTERNALLY DISPLACED PERSONS - PROFESSOR VICTOR SEMAWON AKRAN; ADAMU HENRY DANLAMI GAIYA (International Studies Journal)
This article titled “Armed Banditry in Adaraland: A Study of Humanitarian Crisis and the Plight of the Internally Displaced Persons” dissects incidences of banditry and the experiences of the internally displaced persons in Adaraland. It explores the level of displacement of persons in various villages and the numbers of people who ran away as seen on the field through extensive research carried out in the affected areas. The research shows, in relative detail, the villages affected by the activities of banditry and the plight of the deprived persons. The study finds, among other things, that banditry in these areas was a ploy to destabilise Adaraland and open it up to occupation by non-Adara people. The paper uses oral interview as primary sources of data collection by meeting people who were directly affected or witnessed the events. The study concludes that the media has down played the level of destruction of lives and properties in Adaraland, through under reporting and inadequate publicity as against similar attacks/happenings in other areas of Kaduna State facing similar menace.